Pastoral Narrative Disclosure: A Community Chaplaincy Evaluation of an Intervention Strategy for Addressing Moral Injury - Carey, Lindsay B; Bambling, Matthew; Jamieson, Nikki; Bakhurst, Melissa G; Koenig, Harold G (Health and Social Care Chaplaincy, 2025)
This study presents a community chaplaincy evaluation of pastoral narrative disclosure (PND) as a structured intervention for addressing moral injury (MI) among individuals who have experienced morally injurious events. Pastoral narrative disclosure is an evidence-based, eight-stage pastoral counselling, guidance and education framework that integrates the principles of both adaptive disclosure and confessional narrative. Previously, PND training was evaluated exclusively among Australian military chaplains (n = 201; Carey et al., 2024). In contrast, this evaluation focuses on community chaplains (n = 76), representing diverse organizations in Australia, including police, healthcare, welfare, prison, school, ambulance and veteran sectors. All participating community chaplains completed the Australian Defence Force Chaplaincy Moral Injury Skills Training (MIST) programme, culminating in the final praxis stage of PND. The evaluation revealed high overall satisfaction with the MIST-PND strategy, with participants reporting a mean satisfaction score of 4.88 out of 5 (n = 76), aligning closely with the satisfaction ratings obtained from military chaplains (? = 4.73/5; n = 201). Qualitative feedback was thematically collated, indicating widespread satisfaction with the (i) MIST programme, (ii) PND strategy, (iii) presenters and (iv) practical application role-plays. A diverse range of suggestions are also noted for potential improvement. Overall, the findings are consistent with those from the military chaplaincy evaluation, highlighting the utility of PND within community contexts. Despite several limitations, the results support the broader application of PND in addressing MI, particularly in community health, veteran and welfare settings, as well as among first responders. These findings justify further implementation of PND and additional research to assess its effectiveness across non-military sectors.